Michael Pertschuk papers - Pertschuk, Michael, 1933-; Pertschuk, Michael, 1933-; Pertschuk, Michael, 1933-; Pertschuk, Michael, 1933-
Correspondence, memoranda, speeches, statements, writings, research material, subject files, biographical material, and other papers primarily concerning Pertschuk's work in the area of consumer protection. Part I relates chiefly to his career in the Federal Trade Commission (FTC) covering regulation of antitrust and consumer issues in four areas: energy, food, health, and transportation. Includes drafts of Pertschuk's book, Revolt Against Regulation: The Rise and Pause of the Consumer Movement (1982) and of his book on citizen group lobbying strategies, Giant Killers (1986). Other papers document his work with the Senate Commerce Committee (1964-1977) and his trip to China (1976).
Part II documents Pertschuk's work after leaving the commission in 1984 and focuses on public interest activism especially the issue of tobacco control. Includes drafts of Smoke in Their Eyes: Lessons in Movement Leadership from the Tobacco Wars. Individuals represented include Stanton A. Glantz, David A. Kessler, C. Everett Koop, and Michael L. Myers.
Correspondents include Jack Anderson, Patricia Price Bailey, David Brinkley, Jimmy Carter, David Cohen, John D. Dingell, James Florio, Lewis H. Goldfarb, David Horowitz, George William Koch, Warren Grant Magnuson, Colman McCarthy, James Clifford Miller III, Walter F. Mondale, Edmund S. Muskie, Ralph Nader, Victor S. Navasky, Esther Peterson, Robert Pitofsky, Alan A. Ransom, Ronald Reagan, David Ainsworth Rice, Warren B. Rudman, Alan K. Simpson, Philip M. Stern, Robert S. Strauss, Jack H. Watson, Jr., and Caspar W. Weinberger.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Federal trade commissioner, lawyer, and lobbyist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Anderson, Jack, -- 1922-2005 -- Correspondence; Bailey, Patricia Price, -- 1937- -- Correspondence; Brinkley, David -- Correspondence; Carter, Jimmy, -- 1924- -- Correspondence; Cohen, David, -- 1936- -- Correspondence; Dingell, John D. -- Correspondence; Florio, James J., -- 1937- -- Correspondence; Glantz, Stanton A; Goldfarb, Lewis H. -- Correspondence; Horowitz, David, -- 1937- -- Correspondence; Kessler, David A., -- 1951-; Koch, George William, -- 1926- -- Correspondence; Koop, C. Everett -- 1916-2013.; Magnuson, Warren G. -- 1905-1989 -- Correspondence; McCarthy, Colman -- Correspondence; Miller, James Clifford -- Correspondence; Mondale, Walter F., -- 1928- -- Correspondence; Muskie, Edmund S., -- 1914-1996 -- Correspondence; Nader, Ralph -- Correspondence; Navasky, Victor S. -- Correspondence; Peterson, Esther, -- 1906-1997 -- Correspondence; Pitofsky, Robert -- Correspondence; Ransom, Alan A. -- Correspondence; Reagan, Ronald -- Correspondence; Rice, David Ainsworth, -- 1940- -- Correspondence; Rudman, Warren B. -- Correspondence; Simpson, Alan K. -- Correspondence; Stern, Philip M. -- Correspondence; Strauss, Robert S. -- Correspondence; Watson, Jack H., -- 1938- -- Correspondence; Weinberger, Caspar W. -- Correspondence; United States. -- Congress. -- Senate. -- Committee on Commerce; United States. -- Federal Trade Commission; Antitrust law; Citizens' associations; Consumer protection; Energy industries -- Law and legislation -- United States; Food law and legislation -- United States; Lobbying; Medical care -- Law and legislation -- United States; Public interest -- United States; Tobacco industry -- United States; Tobacco -- Law and legislation -- United States; Trade regulation -- United States; Transportation -- Law and legislation -- United States; China -- Description and travel; United States -- Politics and government -- 1977-1981.; United States -- Politics and government -- 1981-1989.; Lawyers; Lobbyists